Review of the Paraplea Esaki & China (Hemiptera: Heteroptera: Nepomorpha: Pleidae) of Australia, with description of a new species - Cook, Jerry L. (Zootaxa, 2021)
The family Pleidae is represented in Australia only by members of the genus Paraplea. Paraplea brunni (Kirkaldy, 1898) has a widespread distribution in Australia and is also known from New Guinea. Paraplea halei (Lundblad, 1933) appears to be an endemic species occurring only in the southeastern part of Australia. The widespread species P. liturata (Fieber, 1844) occurs in Australia but only in the Northern Territory and Western Australia. The description of P. bifurcata n. sp. documents a fourth pleid species, being known only from the Northern Territory. Paraplea bifurcata n. sp. is easily differentiated from other species of Paraplea by having a bifurcated abdominal keel. An identification key and discussion of morphological characters of the four species of Paraplea from Australia is given.